Anatomic variations in the palmar cutaneous branch of the median nerve among adults in Lagos, Nigeria - Bolaji O Mofikoya (Nigerian Journal of Surgery, 2012)
Dysesthesias due to palmar cutaneous branch of median nerve injuries infrequently follow carpal tunnel release surgeries. Objective: To determine the course of palmar cutaneous branch of the median nerve in wrist of adult Nigerians, identify the common variations, determine its relations to the palmaris longus (PL) in the region of the distal wrist crease. And on these basis, suggest a safe incision for carpal tunnel surgery in Nigerians. Materials and Methods: Detailed anatomic dissection of the palmar cutaneous branch of the median nerve was carried out with the aid of a loupe magnification on 40 Nigerian cadaver wrists. The origin, course in the distal forearm, wrist and proximal palm was traced. Measurements of the distances between the radial and ulnar branches of the nerve and the PL were made. The distance between origin of the nerve and the distal wrist crease was measured as well. The common branching pattern of the nerve was noted. Results: The palmar cutaneous branch of the median nerve was present in all dissected wrists. The mean distance of the radial branch to PL was 0.81 cm (SD ± 0.3 cm), while the ulnar branch was 0.3 cm (SD ± 0.1 cm). from same structure. The mean distance from the origin to the distal wrist crease is 4.5 cm (SD ± 2.1 cm). We noted the terminal distal branching pattern of the nerve to be highly variable. Conclusion: The Palmar cutaneous branch of the median nerve is safe with an incision made at least 0.5 cm ulnar to the PL in carpal tunnel surgeries in Nigerians.